2019
DOI: 10.5114/amsad.2019.87002
|View full text |Cite
|
Sign up to set email alerts
|

Aortic intima-media thickness can be used to determine target organ damage in adult patients with coronary artery disease risk factors

Abstract: Introduction: We aimed to evaluate the relationship between abdominal aortic intima-media thickness (AA-IMT) and thoracic aortic intima-media thickness (TA-IMT) values and to investigate their relationship with common carotid intima-media thickness (CC-IMT) in patients with coronary artery disease (CAD) risk factors. Material and methods: This study included 100 patients who underwent transesophageal echocardiography (TEE) examination for different reasons with at least one CAD risk factor. CC-IMT, AA-IMT, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…According to the ESH/ESC hypertension guidelines, the relationship of IMT with CVD risk is continuous, and carotid IMT >0.9 mm has been reconfirmed as a marker of asymptomatic organ damage ( 29 ). For the aortic arch, a cutoff value of ≥1.2 mm was chosen as IMT in the aortic arch usually is higher than in other vessels based on the findings reported by Bulut et al albeit this cutoff was based on a group of patients with risk factors for coronary atherosclerosis ( 30 ). It is also necessary to keep in mind that IMT is an age-dependent value ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the ESH/ESC hypertension guidelines, the relationship of IMT with CVD risk is continuous, and carotid IMT >0.9 mm has been reconfirmed as a marker of asymptomatic organ damage ( 29 ). For the aortic arch, a cutoff value of ≥1.2 mm was chosen as IMT in the aortic arch usually is higher than in other vessels based on the findings reported by Bulut et al albeit this cutoff was based on a group of patients with risk factors for coronary atherosclerosis ( 30 ). It is also necessary to keep in mind that IMT is an age-dependent value ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff value of ≥0.9 mm was chosen due to the latest European Society of Hypertension/European Society of Cardiology (ESH/ESC) hypertension guidelines ( 29 ). For the aortic arch a higher cutoff value was chosen due to generally higher aortic arch IMT values among our healthy controls, according to results from earlier studies ( 30 ). Plaques were assessed regarding echogenicity (low–medium–high), distribution, irregularity (homogenicity or heterogenicity) and cap (smooth surface or ulceration).…”
Section: Methodsmentioning
confidence: 99%
“…Many previous studies have shown that AAIMT is a marker of preclinical atherosclerosis in children and adolescents. [17][18][19] Although the evaluation of AAIMT with recently developing devices has become of interest in adult patients, [20][21][22][23] there is not much data due to the restriction of the examination mainly caused by abdominal adipose tissue. Nevertheless, the proportion of patients with missing data due to a visualizing problem has been reported to be as low as 7% in a study conducted on adults.…”
Section: Discussionmentioning
confidence: 99%
“…They also identified increased AAIMT as an indicator of target organ damage. 22 A recent study demonstrated that the AAIMT value is more useful than the cIMT value as an indicator of macrovascular organ involvement in hypertensive patients. 20 Our results are consistent with studies comparing AAIMT and cIMT values which were conducted on adults; AAIMT was superior to cIMT in predicting intermediate or high SS.…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, an American Heart Association (AHA) conference concluded that CIMT "can now be considered for further clarification of CHD risk assessment at the request of a physician", provided that it is performed by an experienced laboratory [9]. In a very recent study conducted by Bulut et al, CIMT was also reported to determine the target organ damage in patients with CAD [10]. CIMT was significantly linked to CVDs including myocardial infarction, transient ischaemic attack, etc.…”
Section: Introductionmentioning
confidence: 99%